2014
DOI: 10.2139/ssrn.2518572
|View full text |Cite
|
Sign up to set email alerts
|

Trade Policy Substitution: Theory and Evidence from Specific Trade Concerns

Cosimo Beverelli,
Mauro Boffa,
Alexander Keck

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 28 publications
(43 reference statements)
1
30
0
Order By: Relevance
“…Using data on specific trade concerns (STCs), Beverelli, Boffa and Keck (2014) find clear substitutability between past reductions in applied tariffs and SPS measures in both developed and developing economies, and same negative correlation between tariffs and TBTs only in developed countries. In line with these results, however, from the exporting country perspective, Orefice (2015) shows that lowering tariff by 10% corresponds to a 0.18% and 0.36% higher probability of observing an STC on SPS and TBT respectively.…”
Section: Ntms Tariffs and Trade In The Literaturementioning
confidence: 94%
“…Using data on specific trade concerns (STCs), Beverelli, Boffa and Keck (2014) find clear substitutability between past reductions in applied tariffs and SPS measures in both developed and developing economies, and same negative correlation between tariffs and TBTs only in developed countries. In line with these results, however, from the exporting country perspective, Orefice (2015) shows that lowering tariff by 10% corresponds to a 0.18% and 0.36% higher probability of observing an STC on SPS and TBT respectively.…”
Section: Ntms Tariffs and Trade In The Literaturementioning
confidence: 94%
“…The intuition behind this absence of strong priors on the relationship can be illustrated by the theoretical work of Beverelli et al (). They take product standards as the available NTM and in their base model assume that NTMs such as product standards are unambiguously (marginal) cost increasing .…”
Section: Conceptual Framework and Empirical Methodologymentioning
confidence: 99%
“…Another stream of this empirical literature examines NTMs as specific trade concerns for technical barriers to trade (TBT) and sanitary and phytosanitary measures (SPS). Beverelli et al () show that policy substitution between tariffs and SPS is observed for both developed and developing world, but in the TBT sample this holds only in developed countries. Orefice () reports that as a consequence of tariff cuts, SPS and TBT measures are used to restrict trade.…”
Section: Literaturementioning
confidence: 96%
See 1 more Smart Citation
“…There have been a few, but insightful number of studies investigating whether NTMs are increasingly used as protectionist tools (Beverelli, Boffa, and Keck, 2014;Calo-Blano and Naya, 2005;Grundke and Moser, 2014;Kee, Neagu, and Nicita, 2008;Nordas and Ragoussi, 2015). Nonetheless, little is known on whether EU's usage of pesticide standards have protectionist intent.…”
Section: Introductionmentioning
confidence: 99%